Why Do Some Countries Manage to Extract Growth from Foreign Aid? - Ruhashyankiko, Jean-Francois (IMF Working Papers; Working Paper, 2005)
Aid is primarily given to governments whereas the engine of sustained growth is the private sector. It is therefore illusory to investigate the impact of aid on growth without considering the impact of government interventions on the private sector. The model shows how these interventions improve capacity utilization and growth. However, distortionary interventions can also cause capacity underutilization and an increase in the informal economy, that is, the very market failures the interventions initially sought to address. Countries that fall into this trap are characterized by insufficient credibility in promoting the private sector, which translates into aid dependence and slower growth over time. The empirical evidence is supportive. This paper finds that aggregate aid has a positive impact on growth (even without diminishing returns) but the impact is substantially smaller for low-income countries.